THE DEVELOPMENT AND OPPORTUNITIES OF THE HALAL INDUSTRY IN INDONESIA (International Conference on Social and Islamic Studies, 2022)
Halal is a concept in Islamic economics where there are established rules so that an end result orprocess is called halal. This study aims to analyze the development and opportunities of the halalindustry in Indonesia using quantitative descriptive methods. For Muslims, halal is a must or acondition that must be met for the food consumed, the services used to the standard of theprocess itself. Halal covers various aspects including banking and finance, food, tourism,pharmacy, fashion, media. Indonesia is a country where the majority of the people are Muslim.Logically, the need for halal products and services should be a necessity. Indonesia is the largestmarket for halal food and beverages. Based on a report from the State of Global IslamicEconomy Report 2022, Muslims spend US$2 trillion by 2021 across industries. Year-on-yeargrowth of 8.9% from 2020, with Islamic finance in 2021, up 7.8%, from 2020. The results of thestudy show that every year the halal industry develops, this cannot be separated from the role ofthe government in regulating halal regulations.